Rotational Diffusion of Rhodopsin-Digitonin Micelles Studied by Transient Photodichroism - Strackee, L. (1971)
The transient photodichroism induced by a 0.80 sec plane-polarized light flash in a rhodopsin-digitonin mixture at about -70°C was compared with a theoretical description of the effect. It was concluded that the transient dichroism is entirely due to rotational diffusion of the pigment molecules. When the rhodopsin-digitonin micelles are assumed to be rotationally symmetric it was found from the observed relaxation time that the axial ratio is probably less than 2. The initial photodichroism after each flash as a function of the number of flashes was shown to obey an equation derived for the photochemical equilibrium reaction between rhodopsin, lumirhodopsin, and isorhodopsin. The absolute quantum efficiency of the transition of rhodopsin to lumirhodopsin was found to be equal, within experimental error, to the quantum efficiency of bleaching rhodopsin at room temperature.